Concrete pavement material as well as preparation method and application thereof
By using optimized particle size recycled aggregates from construction waste, waste tire rubber particles, and industrial solid waste admixtures in synergistic enhancement with nanofillers, the resource consumption and carbon emission problems of traditional concrete pavement materials have been solved, and the compressive strength and toughness have been improved, resulting in high-performance recycled concrete pavement materials.
Patent Information
- Application Number
- CN202510731494.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-03
- Publication Date
- 2025-10-17
AI Technical Summary
Traditional concrete pavement materials have problems in terms of resource consumption and carbon emissions, and the performance of recycled aggregates deteriorates, leading to a decrease in strength, making it difficult to effectively utilize recycled resources such as construction waste and waste tires.
By using recycled aggregates from construction waste with optimized particle size, waste tire rubber granules, and industrial solid waste admixtures, combined with nanofillers and modified plant fibers, a three-phase synergistic reinforcement system of rigid-flexible-cementing is formed. Surface modification treatment is used to improve interfacial bonding strength and material toughness.
It significantly improves the compressive strength and elastic modulus of concrete, extends the cracking time, increases the waste resource utilization rate and reduces life cycle carbon emissions, thus achieving high-performance pavement materials.
Smart Images

Figure BDA0005432075090000061
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of building materials, in particular to a concrete pavement material and a preparation method and application thereof. BACKGROUND
[0002] As a core component of modern transportation infrastructure, concrete pavement materials are widely used in municipal roads, highways, airport runways, port terminals and industrial sites, etc. Their performance is directly related to road service life, driving safety and life cycle economy. Traditional concrete pavement materials use natural aggregates (sand and gravel) and cement as main raw materials, form a rigid structure through cementation, and have high compressive strength and excellent durability. However, with the continuous expansion of global infrastructure construction, the technical bottlenecks of traditional materials are increasingly prominent, mainly in the following two aspects:
[0003] 1. Resource consumption problem: The overexploitation of natural aggregates has caused serious ecological crisis. The annual production of concrete consumes a large amount of resources, leading to riverbed erosion, destruction of biological habitats and imbalance of landforms. In addition, the annual production of large amounts of waste such as construction waste, waste tires and industrial solid waste (such as fly ash and slag) has exceeded 10 billion tons, but the utilization rate of traditional concrete systems for these renewable resources is less than 30%, causing "resource-waste" double waste.
[0004] 2. Carbon emission problem: Cement production is the main source of carbon emissions in the concrete industry chain. The calcination process of cement clinker releases a large amount of process CO2, while fuel combustion and power consumption further aggravate carbon emissions. The life cycle carbon footprint of traditional concrete pavement materials (including raw material mining, production, transportation, construction and maintenance) is not conducive to environmental protection.
[0005] Some technologies partially alleviate resource pressure by adding industrial solid wastes such as fly ash and slag, but still have the following limitations: Performance degradation of recycled aggregates: The recycled aggregate of construction waste has high porosity and high water absorption due to the attached mortar, and the strength of concrete significantly decreases when the substitution rate exceeds 30% under traditional process. SUMMARY
[0006] The present application aims to at least solve one of the problems in the prior art. To this end, the present application proposes a concrete pavement material.
[0007] The present application also proposes a preparation method of the above-mentioned concrete pavement material.
[0008] The present application also proposes the application of the above-mentioned concrete pavement material.
[0009] According to one aspect of the present application, a concrete pavement material is provided, comprising the following raw materials: cementitious material, auxiliary cementitious material, aggregate, water reducing agent and reinforcing agent, the auxiliary cementitious material comprises industrial solid waste admixture, the industrial solid waste admixture comprises fly ash-slag composite powder and nano filler, the nano filler comprises nano aluminum oxide and nano silicon dioxide; the aggregate comprises natural fine aggregate, recycled fine aggregate and recycled coarse aggregate, the recycled fine aggregate comprises waste tire rubber particles, and the recycled coarse aggregate comprises construction waste recycled aggregate; the mass ratio of the recycled fine aggregate to the aggregate is 5-15%; the mass ratio of the recycled coarse aggregate to the aggregate is 35-45%;
[0010] The construction waste recycled aggregate comprises first particle size construction waste, second particle size construction waste and third particle size construction waste, and the mass ratio of the first particle size construction waste, the second particle size construction waste and the third particle size construction waste is 1:0.8-1.2:1.2-1.5, the particle size of the first particle size construction waste is d1, the particle size of the second particle size construction waste is d2, and the particle size of the third particle size construction waste is d3, and d 1~3 The value range of d is as follows: 10mm≤d1<15mm; 15mm≤d2<20mm; 20mm≤d3≤30mm.
[0011] The concrete pavement material according to the embodiment of the present application has at least the following beneficial effects: the construction waste recycled aggregate with continuous grading of particle size is combined with waste tire rubber particles and industrial solid waste admixture in the present application, forming a rigid-flexible-cementitious three-phase synergy, so that the compressive strength of the concrete is improved by more than 52% compared with traditional recycled concrete; the three-phase synergistic reinforcement system of the present application greatly improves the replacement rate of recycled aggregate; it significantly improves the resource utilization rate of waste materials, significantly reduces the life cycle carbon emission rate, and simultaneously realizes the high performance of pavement materials. The present application uses nano filler modification technology, uses nano aluminum oxide and nano silicon dioxide as composite reinforcing components, and significantly improves the elastic modulus and flexural strength of the concrete through the synergistic effect of the two. While maintaining the excellent toughness of the material, the concrete pavement material is endowed with high toughness, forming a composite reinforcement system with rigidity and toughness.
[0012] According to some embodiments of the present application, the waste and old tire rubber particles are pretreated waste and old tire rubber particles, and the pretreatment comprises the following steps: soaking with a strong alkali solution (such as sodium hydroxide, etc.). The surface of the waste and old tire rubber particles is modified by using a strong alkali solution such as sodium hydroxide, so as to reconstruct the micro-morphology of the rubber surface and introduce active groups. This process can effectively etch the inert layer on the surface of the rubber, increase the roughness and expose the polar functional groups (such as hydroxyl and carboxyl), so as to promote the chemical bonding and mechanical engagement of the rubber particles with the cement hydration products (especially calcium hydroxide crystals), thereby significantly improving the bonding strength of the rubber-cement matrix transition zone. The modified rubber concrete composite material maintains the characteristics of light weight and high elasticity, and its flexural strength, impact resistance and durability are synergistically enhanced.
[0013] According to some embodiments of the present application, the pretreatment comprises the following steps: soaking with a sodium hydroxide solution with a mass fraction of 5-10% at 60-80°C for 12-48h.
[0014] According to some embodiments of the present application, the particle size of the natural fine aggregate and the recycled fine aggregate is less than 5mm.
[0015] According to some embodiments of the present application, the mass ratio of the natural fine aggregate, the recycled fine aggregate and the recycled coarse aggregate is 14-15:2-8:16-20.
[0016] According to some embodiments of the present application, the raw materials of the fly ash-slag composite powder include blast furnace slag and fly ash, and the mass ratio of the blast furnace slag and the fly ash is 35-45:15-20.
[0017] According to some embodiments of the present application, the particle size of the nano-alumina in the nano-filler is 5-100nm, and the particle size of the nano-silica is 5-50nm.
[0018] According to some embodiments of the present application, the mass ratio of the nano-filler in the raw materials of the auxiliary cementitious material is 1.5-3%.
[0019] According to some embodiments of the present application, the mass ratio of the nano-alumina and the nano-silica in the nano-filler is 3:1.5-2.5. When the two are mixed in this ratio, a gradient transition "core-shell" structure can be better formed, and the stress field can be uniformly distributed at the nano scale.
[0020] According to some embodiments of the present application, the water reducing agent is a polycarboxylic acid water reducing agent.
[0021] According to some embodiments of the present application, the reinforcing agent includes polymer fibers and glass fibers.
[0022] According to some embodiments of the present application, the reinforcing agent further comprises modified plant fiber. The addition of green low-carbon modified plant fiber can not only improve the toughness of concrete through physical blocking and bridging, but also provide a certain amount of water release compensation. In addition, the bridging effect of the fiber can also reduce the drying shrinkage cracks and reduce the shrinkage of the pavement concrete material.
[0023] According to some embodiments of the present application, the lengths of the polymer fiber, the glass fiber and the modified plant fiber are controlled at 5-15 mm respectively.
[0024] According to some embodiments of the present application, the mass ratio of the polymer fiber and the glass fiber is (2-4):(1-3).
[0025] According to some embodiments of the present application, the volume ratio of the modified plant fiber in the concrete pavement material is 0.2-0.4%.
[0026] According to some embodiments of the present application, the preparation method of the modified plant fiber comprises the following steps: treating the plant fiber with a strong alkali solution at 55-70°C for 2-3h.
[0027] According to some embodiments of the present application, the plant fiber is selected from at least one of sisal fiber, bamboo fiber or flax fiber. The plant fiber (such as sisal fiber, coconut shell fiber) forms a three-dimensional random distribution network structure in the concrete, effectively bridging the micro-cracks and inhibiting the crack propagation.
[0028] According to some embodiments of the present application, the mass percentage of sodium hydroxide in the sodium hydroxide solution is 2-6%.
[0029] According to some embodiments of the present application, the cementitious material comprises at least one of Portland cement, sulfoaluminate cement and aluminate cement.
[0030] According to some embodiments of the present application, the Portland cement comprises at least one of ordinary Portland cement, fly ash Portland cement, slag Portland cement, pozzolan Portland cement and composite Portland cement.
[0031] According to some embodiments of the present application, the mass ratio of the cementitious material, the auxiliary cementitious material, the aggregate, the water reducing agent, the reinforcing agent is 25-28:7-15:30-55:0.1-0.5:1.5-2.
[0032] According to some embodiments of the present application, the raw material of the concrete pavement material further comprises water, and the mass percentage of water is 10-20%.
[0033] According to another aspect of the present application, a preparation method of the concrete pavement material is also provided, comprising the following steps:
[0034] The cementitious material, the auxiliary cementitious material, the aggregate, the water reducing agent and the reinforcing agent are combined, and the concrete pavement material is obtained.
[0035] According to still another aspect of the present application, the concrete pavement material is also applied to road construction materials.
[0036] According to some embodiments of the present application, the road construction material is an airport pavement construction material.
[0037] According to still another aspect of the present application, a concrete is also provided, and the preparation raw material of the concrete comprises the concrete pavement material.
[0038] According to the application of the embodiments of the present application, at least the following beneficial effects are achieved: the pavement constructed by the concrete pavement material of the present application has higher compressive strength, stronger anti-cracking performance and better toughness, and the pavement constructed by the concrete pavement material has significantly improved wear resistance.
[0039] Additional aspects and advantages of the present application will be described in the following description, become apparent from the following description, or be learned by practice of the present application. DETAILED DESCRIPTION
[0040] The concept and the technical effects of the present application will be described in detail below with reference to the embodiments. Obviously, the described embodiments are only some of the embodiments of the present application, but not all the embodiments. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative effort are within the scope of the present application. The test methods used in the embodiments are conventional methods unless otherwise specified. The materials, reagents, etc. used in the embodiments are commercially available unless otherwise specified. The same parameters in the same embodiment have the same values unless otherwise specified. The embodiments described below are exemplary and are used to explain the present application, but cannot be understood as limiting the present application.
[0041] In the description of the present application, the description of the terms "some embodiments" and the like means that the specific features, structures, materials or characteristics described in connection with the embodiments or examples are included in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0042] In the description of the present application, if there is described first, second, etc. is only for the purpose of distinguishing technical features, and can not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features or implicitly indicating the order of the indicated technical features.
[0043] The following examples and comparisons are useful, for example, the materials used are as follows:
[0044] The cementing material uses P·O 42.5 Portland cement.
[0045] The natural fine aggregate uses river sand with fineness modulus of 2.74.
[0046] The water reducing agent uses M13 high water-reducing polycarboxylic acid water-reducing agent purchased from Jiangsu Aolite New Material Co., Ltd.
[0047] The polypropylene fiber is used as the polymeric fiber.
[0048] The lengths of the polymeric fiber, glass fiber and modified plant fiber are controlled at 5-15 mm respectively.
[0049] The particle size of the nano-aluminum oxide is 5-100 nm, and the particle size of the nano-silicon dioxide is 5-50 nm.
[0050] The raw material of the fly ash-slag composite powder is blast furnace slag and fly ash, and the mass ratio of the blast furnace slag and fly ash is 40:18 (20:9).
[0051] If the waste tire rubber particles are pretreated, the pretreatment step is as follows: the waste tire rubber particles are soaked in a sodium hydroxide solution with a mass fraction of 8% at 60℃ for 24h at a liquid-mass ratio of 15mL:1g. The waste tire rubber particles without pretreatment refer to the same source as the pretreated ones except that they are not pretreated.
[0052] The mass ratio of the first particle size construction waste, the second particle size construction waste and the third particle size construction waste of the construction waste recycled aggregate used in the embodiment is 1:1:1.2. The construction waste recycled aggregate used in Comparative Example 1 is the first particle size construction waste and the second particle size construction waste, wherein the mass ratio of the first particle size construction waste and the second particle size construction waste is 1:1. The construction waste recycled aggregate used in Comparative Example 2 is the first particle size construction waste and the third particle size construction waste, wherein the mass ratio of the first particle size construction waste and the third particle size construction waste is 1:1.2. The construction waste recycled aggregate used in Comparative Example 3 is the first particle size construction waste, the second particle size construction waste and the third particle size construction waste, wherein the mass ratio of the first particle size construction waste, the second particle size construction waste and the third particle size construction waste is 1:1:2. The construction waste recycled aggregate used in Comparative Example 4 is the first particle size construction waste, the second particle size construction waste and the third particle size construction waste, wherein the mass ratio of the first particle size construction waste, the second particle size construction waste and the third particle size construction waste is 1:1:0.8. The construction waste recycled aggregate used in Comparative Example 5 is the same as that in Example 1, but the particle size distribution thereof is not controlled. The natural fine aggregate and the recycled coarse aggregate are used in Comparative Example 6, wherein the natural coarse aggregate comprises the gravel aggregate with the same particle size and mass ratio distribution as that in Example 1. The natural coarse aggregate used in Comparative Example 10 is the same as that in Comparative Example 6.
[0053] The modified plant fiber used in the embodiment refers to the sisal fiber soaked in 3wt% NaOH solution at 60°C for 2h, with a liquid-solid ratio of 10mL:1g.
[0054] Examples and Comparative Examples
[0055] The raw materials are weighed according to the mass parts (the total mass parts are 100 parts) listed in Table 1 below, and then the concrete pavement materials of the examples and the comparative examples are obtained.
[0056] Table 1
[0057]
[0058] The concrete pavement materials in the above examples and comparative examples are used to prepare concrete, which comprises the following steps:
[0059] Mixing and molding. The materials weighed according to the proportions are mixed and stirred uniformly, and then put into the standard mold corresponding to the test conditions.
[0060] Test Example 1: Compressive Strength Test
[0061] The 28d compressive strength (MPa) of the concrete prepared in the above examples and comparative examples was detected according to the 5th part of GB / T50081-2019 "Standard Test Methods for Physical and Mechanical Properties of Concrete", and the greater the compressive strength, the better the bearing capacity of the concrete. A cubic steel mold with a size of 150mm*150mm*150mm was used.
[0062] Test Example 2 Dynamic Elastic Modulus Test
[0063] The dynamic elastic modulus (MPa) of the concrete prepared in the above examples and comparative examples was detected according to the 5th part of GB / T50082-2024 "Standard Test Methods for Long-term Performance and Durability of Concrete", and the smaller the dynamic elastic modulus, the better the flexibility of the concrete. A prism specimen with a size of 100mm*100mm*400mm was used.
[0064] Test Example 3 Cracking Time Test
[0065] The cracking time (h) of the concrete prepared in the above examples and comparative examples was detected according to JC / T2234-2014 "Test Method for Early Age Cracking Resistance of Cement", and the longer the cracking time, the better the cracking resistance of the concrete.
[0066] The test results are shown in Table 2 below.
[0067] Table 2
[0068] Compressive strength (28d, MPa) Dynamic elastic modulus (MPa) Cracking time (h) Example 1 52 2.54 x 10 4 ]] 186 Example 2 48 2.42 x 10 4 ]] 175 Example 3 40 2.85 x 10 4 ]] 155 Example 4 38 2.77 x 10 4 ]] 154 Example 5 42 2.94 x 10 4 ]] 117 Example 6 39 2.56 x 10 4 ]] 140 Comparative Example 1 28 2.82 x 10 4 ]] 141 Comparative Example 2 27 2.69 x 10 4 ]] 140 Comparative Example 3 32 2.65 x 10 4 ]]> 140 Comparative Example 4 30 2.73 x 10 4 ]] 138 Comparative Example 5 28 2.79 x 10 4 ]] 141 Comparative Example 6 32 2.74 x 10 4 ]] 139 Comparative Example 7 32 2.78 x 10 4 ]] 132 Comparative Example 8 32 3.24 x 10 4 ]] 110 Comparative Example 9 30 3.28 x 10 4 ]] 116 Comparative Example 10 25 3.79 x 10 4 ]] 41
[0069] The application scheme adopts multi-stage particle size construction waste recycled aggregate to form a close-packed structure, reduces the void ratio, enhances the skeleton support effect, and greatly improves the compressive strength of the concrete pavement. The pretreated waste tire particles can better improve the toughness of the concrete, the strong alkali etching removes the surface inert layer, exposes the polar groups such as hydroxyl and carboxyl groups, and enhances the chemical bonding with the cement hydration product. Surface roughening promotes mechanical engagement, improves the bonding strength of the rubber-cement interface transition zone (ITZ), and alleviates the strength loss caused by the incorporation of rubber, while retaining its energy absorption properties and improving impact toughness. Chemically modified (such as alkali treatment) plant fibers remove lignin, expose cellulose hydroxyl groups, and improve hydrogen bonding with cement. Modified plant fibers can better form a three-dimensional network and form a fiber bridging effect; at the same time, nano fillers inhibit microcracks, and plant fibers block macrocracks, which synergistically improve the compressive strength and cracking resistance. Proper control of the ratio of recycled coarse aggregate and recycled fine aggregate realizes the synergistic improvement of strength and toughness; this system realizes the breakthrough improvement of the performance of recycled concrete materials through three-dimensional synergy of molecular scale interface modification, micro-nano scale structure regulation, and macro scale fiber reinforcement, and has environmental protection and engineering applicability.
[0070] The surface of the waste tire rubber particles is modified by using a strong alkali solution such as sodium hydroxide, and by adjusting the solution concentration (such as 5%-10% mass fraction), the treatment temperature (60-80℃) and the immersion time (12-48h), the surface micro-morphology of the rubber is reconstructed and active groups are introduced. This process can effectively etch the inert layer on the surface of the rubber, increase the roughness and expose the polar functional groups (such as hydroxyl and carboxyl groups), promote the chemical bonding and mechanical engagement of the rubber particles and the cement hydration product (especially calcium hydroxide crystals), and significantly improve the bonding strength of the rubber-cement matrix interface transition zone. The modified concrete composite material retains the characteristics of light weight and high elasticity, and its compressive strength, impact resistance and durability are synergistically enhanced.
[0071] The addition of modified plant fibers significantly improves the toughness of the concrete, and also significantly improves its cracking resistance.
[0072] The mechanism of nano-alumina as a modified auxiliary cementitious material mainly reflects in three aspects: first, with the characteristics of high specific surface area, it can significantly enhance the adsorption and regulation ability of free water, and optimize the hydration process of cement particles; second, through the interface chemical reaction between surface hydroxyl and cement hydration product Ca(OH)2, hydration calcium aluminate(C-A-H) with cementation characteristics is generated, and the secondary pozzolanic effect of mineral admixtures is stimulated to promote the generation of nano-scale C-S-H gel in the system, and build a three-dimensional interlocking dense network structure; third, through the template effect to control the crystalline orientation of the interface transition zone(ITZ), the coarse plate-like Ca(OH)2 crystals are refined, the porosity is effectively reduced and the micro-crack initiation is inhibited, so that the compressive strength of concrete is improved and the cracking time is significantly prolonged. Nano-silica improves the pore structure through a dual mechanism: its particle size effect(5-50nm) makes the particles can penetrate into the interior of the cement matrix, and react with Ca(OH)2 in the pozzolanic reaction to generate low calcium-silicon ratio high-strength C-S-H gel; at the same time, the unreacted nanoparticles play a micro-aggregate filling effect, converting capillary pores into gel pores, reducing total porosity and significantly shifting the pore size distribution curve to the left. This optimization of pore structure can reduce the chloride ion diffusion coefficient and provide a sustained enhancement interface for later strength development. Nano-alumina preferentially consumes large-size Ca(OH)2 crystals, while nano-silica focuses on improving the mesopore structure, and cooperatively improves the compressive strength, and also can significantly reduce the dynamic elastic modulus, with excellent toughness characteristics. Especially when the two are mixed at a ratio of 3:2, a gradient transition "core-shell" structure can be formed, achieving uniform distribution of stress field at the nanoscale, thereby having more excellent compressive strength and toughness.
[0073] The above detailed the embodiments of the present application, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of those skilled in the art without departing from the spirit of the present application.
Claims
1. A concrete pavement material, characterized by: The invention comprises the following raw materials: a cementitious material, an auxiliary cementitious material, an aggregate, a water reducing agent and a reinforcing agent, wherein the auxiliary cementitious material comprises an industrial solid waste admixture, the industrial solid waste admixture comprises a fly ash-slag composite powder and a nanofiller, the nanofiller comprises nano alumina and nano silica; the aggregate comprises natural fine aggregate, recycled fine aggregate and recycled coarse aggregate, the recycled fine aggregate comprises waste tire rubber particles, and the recycled coarse aggregate comprises recycled aggregate from construction waste; the recycled fine aggregate accounts for 5 to 15% of the aggregate by mass; the recycled coarse aggregate accounts for 35 to 45% of the aggregate by mass; The recycled aggregate from construction waste includes first-size construction waste, second-size construction waste and third-size construction waste in a mass ratio of 1:0.8-1.2:1.2-1.
5. The particle size of the first-size construction waste is d1, the particle size of the second-size construction waste is d2, the particle size of the third-size construction waste is d3, and the particle size of the d 1~3 The value range is as follows: 10mm≤d1<15mm; 15mm≤d2<20mm; 20mm≤d3≤30mm.
2. The concrete pavement material according to claim 1, characterized in that: The waste tire rubber particles are pretreated waste tire rubber particles, and the pretreatment comprises the following steps: soaking in a sodium hydroxide solution with a mass fraction of 5 to 10% at 60 to 80° C. for 12 to 48 hours.
3. The concrete pavement material according to claim 1, characterized in that: The mass proportion of the nano filler in the raw materials of the auxiliary gelling material is 1.5-3%.
4. The concrete pavement material according to claim 1, characterized in that: The mass ratio of nano-alumina to nano-silicon dioxide in the nano-filler is 3:1.5-2.
5.
5. The concrete pavement material according to claim 1, characterized in that: The reinforcing agent includes polymer fiber and glass fiber, and also includes modified plant fiber.
6. The concrete pavement material according to claim 5, characterized in that: The product is obtained by treating plant fibers with a strong alkaline solution at 55-70°C for 2-3 hours.
7. The concrete pavement material according to any one of claims 1 to 6, characterized in that: The mass ratio of the cementitious material, the auxiliary cementitious material, the aggregate, the water reducing agent and the reinforcing agent is 25-28:7-15:30-55:0.1-0.5:1.5-2.
8. Use of the concrete pavement material according to any one of claims 1 to 7 in road construction materials.
9. The use according to claim 8, characterized in that: The road construction materials are airport pavement construction materials.
10. A concrete, characterized in that: The raw materials for preparing the concrete include the concrete pavement material according to any one of claims 1 to 7.